Humour beckons : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Creative Writing at Massey University, Albany, New Zealand - Sutherland, Jack Robin Atherton (Massey University, 2023)
What is humour? At its worst it might be the drunk person down the pub annoying everyone in the vicinity as they attempt to crack wise. At its best it is one of humanity's greatest unifiers and sources of comfort. The critical component of this MCW thesis explores what brought me to humour, what I discovered during my exploration of some of its performative and literary manifestations, and how this exploration came to affect my own creative output. The creative section of this thesis is a collection of short stories in some of the styles that I have found to be more effective in attaining a higher level of meaning during my exploration of humour in literature and beyond. These include black humour, absurdist fiction, and slapstick short stories.
Keywords: 360201 Creative writing (incl. scriptwriting)